PCS-8 Oyster Shell Powder as Alternatives Macromineral for Synthetic Testosterone - Pudji Astuti; Claude Mona Airin; Alfarisa Nururrozi; . Harimurti (Hemera Zoa, 2018)
Oyster is one of seafood produced in waters, especially in eastern Indonesia. During this time, oyster is known as aphrodisiac agents, an agent that can increase sexual appetite because it can remind testosterone levels and very high nutrient content of zinc, vitamin A iron, calcium, and selenium are also Vitamins A and Vitamin B12. Therefore, the oyster is known as the mineral's potent testosterone-boosting abilities (Matsuda et al., 2003). Zinc is also very important, it can be used as a stimulant of enzymes, hormones and the immune system.Due to the abundance of oysters in Indonesia, only meat of oyster is consumed, while the existing shells are never used to consume and just thrown away. Therefore, a research plan will be made on the use of oyster shell waste, as a precursor of testosterone in Rat (Rattus norvegicus). Since many kinds of oyster, it would be compared among three kinds of oyster shell namely Kerang darah (Anadara granosa), Kerang hijau (Perna viridis) and Kerang keong (Telescopium telescopium).Based on function, Zn inhibits aromatase enzyme which convert estradiol to testosterone as a consequence, testosterone levels will increase (Michell et al. 2012).The purpose of this study were to determine the highest content of Zn among the three types of oyster shell; 2. To measure testosterone levels in rat after given shell powder containing highest Zn.